Optimal Functioning in Sport Psychology: Helping Athletes Find Their "Zone of Excellence" - Sime, W.; Allen, T. W.; Fazzano, C. (Biofeedback, 2001)
Sport psychologists and peak achievement trainers are continuously seeking cutting edge methods of achieving the most expedient route to confidence, trust in one's ability, appropriate focus, composure and explosive power with graceful, efficient movement patterns. This is characteristic of almost all high level performance including team and individual sports, as well as aesthetic performances in music, dance, artistry, etc. All are rewarded when graceful yet powerful movements can be performed with seemingly effortless composure.